Gastric perforation in a dog: Postmortem computed tomography and forensic autopsy findings. (March 2020) - Hamel, Philip E.S.; Stern, Adam W.; Grosso, Federico Vilaplana
Highlights: PMCT was able to identify antemortem gastric perforation in a dog. Forensic autopsy confirmed the gastric perforation and septic peritonitis. Antemortem gastric rupture needs to be differentiated from gastromalacia. Further research is needed to compare PMCT and veterinary forensic autopsy findings. Abstract: The aim of this case report is to describe the postmortem computed tomography (PMCT) and forensic autopsy investigation findings of a case of antemortem gastric perforation in a dog. A 13-year-old, spayed female, pit bull type dog with a recent history of limping, anorexia, and lethargy, was treated with unknown doses of an unknown corticosteroid, grapiprant (a veterinary nonsteroidal anti-inflammatory drug [NSAID]), and omeprazole, prior to euthanasia. PMCT was subsequently completed, followed by confirmatory forensic autopsy. On PMCT images, a full thickness gastric wall discontinuity with confluent luminal and extraluminal gas (pneumoperitoneum) was identified. In the absence of expected additional sites of postmortem intracavitary gas accumulation (pleural, peri-cardial, and intra-articular) the pneumoperitoneum was attributed primarily to antemortem gastric rupture, which precipitated patient decline and subsequent euthanasia. Forensic autopsy revealed gastric ulceration with perforation. Histological evaluation of the perforation site revealed suppurative inflammation and an early healing response. The combined findings of the PMCT and autopsy were compatible with antemortem gastric perforation attributable to the historical concurrent administration of a NSAID and corticosteroid. Given adequate radiologist knowledge and training, antemortem gastric perforation may be differentiated from postmortem gastromalacia with rupture.